Artificial Intelligence in graphic design. Perception of students of a public university institution - Macias Reyes , Katherine Nayeli; Tomalá Gonzabay , Vanessa Alexandra (Scripta Mundi, 2023)
The present research seeks to know the perception of Graphic Design university students from a public university institution on Artificial Intelligence. This new technology is currently generating a lot of controversy, especially due to its great data management capacity and powerful tools for almost all of them. areas of knowledge, particularly in graphic design, this raises great concerns if at some point it will be able to generate its own creativity and replace the work of graphic design professionals. The study is descriptive in nature, the unit of analysis is the ninth semester students of the Graphic Design degree at the University of Guayaquil, the largest public higher education institution in Ecuador, the methodology used is quantitative in nature, the Information was collected through an online survey. The results show divided opinions of graphic design students about the advantages, disadvantages and impact of Artificial Intelligence
Keywords: artificial intelligence; graphic design; automation; creative technology